Obstacles in the Management of School Operational Assistance Funds (BOS) at State Elementary School 1 Koba, Central Bangka Regency - Miwis Leani; Bukman Lian; Alhadi Yan Putra; Kartika Sari (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This research is a type of descriptive qualitative research with data collection techniques through direct and indirect interview methods, field observation, and activity documentation. This study aims to analyze the obstacles experienced in the Management of School Operational Assistance Funds (BOS) at State Elementary School 1 Koba, Central Bangka Regency. In every implementation of activities in schools, both in the field of education and others, there will definitely be an obstacle that can hinder the delivery of educational materials itself, especially in terms of the management of the School Operational Assistance Fund (BOS) of SDN 1 Koba. These obstacles can come from external and internal factors at school. For external obstacles are factors outside the school environment, namely the community. While the internal factor is from the school itself. These problems must always be monitored and then evaluated periodically, anticipated and solutions found by interested parties in the implementation of BOS fund management at SDN 1 Koba.